Art in weightlessness: From outer space to virtual worlds. Issue 1 (1st June 2017) - Murnik, Maja
Space art and art within virtual worlds share conceptual and even ontological commonalities. There are three issues that can be examined in relation to these: the 'problem of gravity', the extensions of the body and the issue of scientific abstraction. Several art projects will be discussed relating to these themes including the Futurist manifestos of aerial art, space poetry, Babeli's Come to Heaven, and Živadinov's Biomechanics Noordung and Noordung:: 1995–2045.